IDENTIFYING PRECURSOR CONDITION FOR “PUTING BELIUNG” EVENT IN PANGKALPINANG - - Siswanto; - Supari (Widyariset, 2012)
This paper discusses an effort to identify the precursor condition for “puting beliung” or tornado-like eventwhich was occured in Pangkalpinang town on January 9, 2008. The analyses has been done based on the dynamicpipe effect of tornado genesis theory. Several data obtained from surface observation as well as the advantage ofsatellite data image were used to identify signal of presence of puting beliung. The result indicates that the putingbeliung event was triggered by the presence of low level wind shear which was supported by favorable surfacecondition such as the existing of enough water vapor aloft indicated by high relative humidity, enough surfaceheating to initiate a rapid cooling of the atmosphere to produce deep convection, and there is an initiation of alocal anomaly surface wind speed to produce low level wind shear. Revealed surface precursor for puting beliungin Pangkalpinang are the rapid increasing the relative humidity one hour in advance, together with rapid drop intemperature and the presence of “horn-like” pressure anomaly.